18F-FDG production procedures as a source of eye lens exposure to radiation. (15th February 2018) - Wrzesień, Małgorzata
Abstract: Decreasing the individual dose limit of exposure to ionizing radiation to the eye lenses means verifying the need for routine monitoring of the eye lenses of workers exposed to ionizing radiation, including those employed in facilities producing radiopharmaceuticals based on short-lived isotopes. This work analyzes the exposure of the eye lenses of employees of centers that produce the isotopes for positron emission tomography, in particular fluorine-18. It takes into account the employment structure and work system of the discussed centers, including in terms of changing the dose limit of exposure to the eye lenses. This work complements the paper by Wrzesień (2018 Australas. Phys. Eng. Sci. Med. submitted), which focused on the exposure of workers' hands to ionizing radiation in radiopharmaceutical production centers. Measurements were carried out using high-sensitivity thermoluminescence detectors (LiF: Mg, Cu, P-MCP-N). The measurements covered 17 employees. Our results show that the highest values of personal dose equivalent H p(3) were recorded for the 18 F-FDG quality control personnel and nurses who injected the radiopharmaceutical in the patients. In the group of nurses, the maximum daily does H p(3) reached a value close to 200 μ Sv. For staff who performed the quality control of the 18 F-FDG, the maximum daily dose of H p(3) exceeded 200 μ Sv. The estimated annual exposure of the eye lenses of workers in these two occupational groups may exceed the new dose limit (20 mSv/year). Results of this study indicate the need for optimization of the procedures related to quality control of radiopharmaceuticals and the injection of 18 F-FDG in patients.